W.G. Armstrong, The Ordinances and Charter of the City of Jeffersonville 15-17, § 3, pt. 10 (1855) - (:unkn) unknown (My University, 1855)
§ 3, pt. 10: Prohibited storing more than twenty-five pounds of gun powder.
Keywords: GUNPOWDER - STORAGE